Comparative study of oxytocic drugs versus negative pressure suction method in management of atonic postpartum hemorrhage in high-risk mothers - Kaur, Jasvir; Kaur, Satwant; Aditi, (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Postpartum hemorrhage (PPH) is the most dreadful obstetric emergency and atonic PPH being most common cause of PPH accounting for 70-80% of cases leading to maternal mortality worldwide. The aim of the present study was to compare efficacy of oxytocic drugs and panicker PPH hemostatic suction cannula in management of postpartum haemorrhage in atonic PPH and to describe an effective, simple and minimally invasive method to avoid excess blood loss. Methods: This study was carried out in Department of Obstetrics and Gynecology, Adesh Medical College and Hospital, Mohri, Kurukshetra. All the high-risk patients who delivered in Adesh Medical College by vaginal delivery and underwent PPH were included in this study. Patients requiring PPH management were admitted to the obstetrics ward and managed. Results: This study included a total of 50 patients, divided equally into two groups. Group A consisted of 25 patients who were managed with medical therapy alone, while Group B included 25 patients who received both medical treatment and management with the Panicker PPH hemostatic suction cannula. In Group A, all patients required more than four minutes for the bleeding to stop. Of these, 15 patients experienced a blood loss between 250-500 ml, and 10 patients had a blood loss ranging from 501-1000 ml. Regarding transfusion requirements, 15 patients did not require any blood transfusion, whereas 6 patients received two units and 4 patients required three units. In contrast, all patients in Group B achieved cessation of bleeding within four minutes of cannula application. Among them, 20 patients had a blood loss of up to 250 ml, and 5 patients had a loss between 251-500 ml. Most patients (20) in Group B did not require any transfusion, and only 5 required a single unit of blood. Conclusions: Management of atonic postpartum hemorrhage with the Panicker suction cannula proved to be highly effective and efficient. The study concludes that the Panicker suction cannula offers a simple, safe, and minimally invasive technique for the prompt control of atonic PPH. It serves as a cost-effective and practical alternative, particularly suited for use in rural or resource-limited settings, thereby contributing significantly to the reduction of maternal morbidity and mortality associated with postpartum hemorrhage.